Sustainable Taxation and The Challenges of AchievingSustainable ‎Development in Developing Countries - A. , Alshujairi Mohammed Huweish; M.‎ , Alkurtani Khaldoun Salman; Abdelqader , Saleh Ammar (International Journal of Accounting and Economics Studies, 2025)
This paper explored how modern tax theory conceptualizes the role of taxation in achieving sustainable ‎development through a critical analysis of contemporary tax frameworks, which have remained the subject of ‎considerable academic and policy debate. The paper highlighted the limited capacity of existing sustainable tax ‎systems to make a meaningful contribution to sustainable development initiatives. It also analyzed the problems ‎and challenges confronting tax systems in developing countries, which create additional obstacles beyond those ‎experienced by developed nations.‎ The paper further examined the specific difficulties that developing countries have encountered in aligning their ‎tax systems with the Sustainable Development Goals. These nations not only shared common global challenges ‎but also grappled with additional, localized obstacles rooted in economic, social, and environmental instability. ‎In response, the paper proposes Voluntary Sustainability Taxes (VSTs) as a potential mechanism for addressing ‎the key barriers that impede sustainable development, particularly within the context of developing economies.‎ Recognizing the complex crises that had affected these nations, the study argued for the diversification of tax ‎structures to include nontraditional, incentive-based tools. It concluded by analyzing the theoretical and ‎practical justifications for adopting VSTs and evaluating their potential to enhance the responsiveness of tax ‎systems to the imperatives of sustainable development.